Assessing Knowledge of Community Pharmacists on Cancer: A Pilot Study in Ghana - Kofi Boamah Mensah; Kofi Boamah Mensah; Varsha Bangalee; Frasia Oosthuizen (Frontiers Media S.A., 2019)
Background: GLOBOCAN estimates that 16,600 cases of cancer occur annually in Ghana. Community pharmacists are the first point of contact to the public due to their accessibility, wide spread and credibility. They are often looked upon to provide first aid and treatment of common illness. They provide health information and support on diseases, e.g., cancer. Their role also extends to the patients' relatives. Thus, the level of knowledge and awareness of community pharmacists are of paramount importance in order to assure best healthcare advice is provided to the public. Goals of this pilot study were; (1) to collect a preliminary data on knowledge of risk factors, signs, and symptoms of cancer, (2) to ascertain the adequacy of the research survey in determining their level of knowledge, (3) to assess the viability of a full-scale study on community pharmacists.Methods: A cross-sectional survey was conducted using a self-administered questionnaire to assess the knowledge of signs and symptoms and risk factors of cancer among 150 community pharmacists.Key Findings: Score for knowledge on cancer among community pharmacists indicated that 76.7% had poor knowledge. Responses of community pharmacists toward a list of warning signs and symptom of cancer indicated poor level of knowledge (82%). Community pharmacists recorded poor level of knowledge (65.3%) on causes and risk factors for cancer. Correlation analysis shows that age has a relation with level of knowledge on signs and symptoms of cancer.Conclusion: This pilot study provided a valuable data which indicated that community pharmacists in Ghana have poor level of knowledge on cancer. The findings obtained from the study agree with findings of other studies conducted in this area which suggest that survey instrument was adequate to assess the knowledge level of community pharmacist in Ghana. Though the response was low, data obtained indicate a viability and need of conducting a full-scale research in this workforce to get a better assessment of the level of knowledge of community pharmacists on cancer in Ghana.